Everybody's fool - Russo, Richard, 1949- (New York : Alfred A. Knopf, 2016)
Russo returns to North Bath, in upstate New York, and the characters of Nobody's Fool, his third novel. The irresistible Sully, who in the intervening years has come by some unexpected good fortune, is now staring down a VA cardiologist's estimate that he only has a year or two left, and he's busy as hell keeping the news from the most important people in his life.
Keywords: City and town life -- New York (State) -- Fiction; Families -- Fiction